Effects of dietary and milking frequency changes and administration of cabergoline on clinical udder characteristics in dairy cows during dry-off. (March 2022) - Franchi, G.A.; Jensen, M.B.; Foldager, L.; Larsen, M.; Herskin, M.S.
Abstract: We investigated the effects of 2 diet energy densities [normal lactation diet (NORM) vs. energy-reduced diet (REDU), both fed for ad libitum intake] and 2 daily milking frequencies [twice (2×) vs. once (1×)] during 1 week before the dry-off day, as well as effects of an injection of either a dopamine agonist [cabergoline (CAB); Velactis, Ceva Santé Animale, Libourne, France; labelled for use only with abrupt dry-off, e.g. no reduction in diet energy density or milking frequency before the last milking] or saline (SAL) following the last milking, on clinical udder characteristics of Holstein cows. During a week before and after the last milking, the following measures were recorded: palpation-based udder firmness and soreness; image-based hock-hock distance; responsiveness to mechanical udder stimulation and degree of udder fill measured with a dynamometer. Before the last milking, REDU cows displayed lower odds of having a firm udder and lower degree of udder fill, as well as lower responsiveness to mechanical udder stimulation, than NORM cows. After the last milking, REDU cows displayed shorter hock-hock distance compared with NORM cows. The effects of milking frequency on the clinical udder characteristics were unclear. Within 24 h following injection, CAB cows showed lower odds of having a firm udder, shorter hock-hock distance, and lower degree of udder fill than SAL cows, irrespective of treatment group before dry-off. In this study, reducing diet energy density prior to dry-off, and to some extent administering the dopamine agonist cabergoline after the last milking, resulted in fewest clinical udder changes. Highlights: Typical dry-off practices constitute a welfare challenge to high-yielding cows. Reducing diet energy content led to the fewest clinical changes of the udder. Effects of milking frequency on the clinical udder characteristics were unclear. Cabergoline limited clinical changes of the udder within 24 h after injection.